(untitled) (Моделювання, керування та інформаційні технології, 2025)
This paper presents a comparative analysis of regional features of seasonal natural gas consumption between the western (Lviv region) and central (Kyiv region) regions of Ukraine. Based on the analysis of experimental data on gas withdrawal by industrial consumers for the period 2017-2022, covering over one million daily consumption records, fundamental differences in seasonal consumption patterns between regions were established. The Lviv region demonstrates moderate seasonality with an amplitude of fluctuations of 0.870 and a correlation coefficient between consumption and temperature ranging from -0.75 to -0.82, while the Kyiv region is characterized by 20-25% higher seasonal irregularity and a correlation coefficient ranging from -0.85 to -0.90. The identified regional differences substantiate the need for differentiated approaches to gas supply planning, development of consumption forecasting methodologies, and reserve capacity management to support Ukraine’s energy security. У цій роботі виконано порівняльний аналіз регіональних особливостей сезонного споживання природного газу між західним (Львівська область) та центральним (Київська область) регіонами України. На основі аналізу експериментальних даних про відбір газу промисловими споживачами за період 2017-2022 років, що охоплюють понад один мільйон записів щоденного споживання, встановлено принципові відмінності у сезонних шаблонах споживання між регіонами. Львівська область демонструє помірну сезонність з амплітудою коливань 0.870 та коефіцієнтом кореляції споживання з температурою від -0.75 до -0.82, тоді як Київська область характеризується на 20-25% вищою сезонною нерівномірністю та коефіцієнтом кореляції від -0.85 до -0.90. Виявлені регіональні відмінності обґрунтовують необхідність диференційованих підходів до планування газопостачання, розроблення методик прогнозування споживання та управління резервними потужностями для підтримки енергетичної безпеки України.